The miracles of Jesus [videorecording (DVD)] / a BBC Discovery Channel co-production in association with Jerusalem Productions ; director and series producer, Jean-Claude Bragard ; producer/director, Anna Cox ; executive in charge of production, Jane Root.. - Bragard, Jean-Claude; Cox, Anna; Gill, Brock; Hodgkins, Tom (BBC Video ; Distributed by Warner Home Video, Inc., 2006)
Join Christian illusionist Brock Gill as he follows the story of Jesus' life by examining the deeds for which he is best remembered - his miracles. Bible events are brought to life through drama and amazing computer graphics.